“They Stopped the Lives of Others”: Stateless Palestinians Facing Bureaucratic Violence in Sweden - Lundberg, Anna (Refuge, 2023)
Official calls for “failed” asylum seekers to leave Sweden ignore the difficulties and harms befalling stateless people who cannot return to previous countries of residence because they lack citizenship. Stateless people are caught in limbo, a position where they have no prospects of return or of attaining a residence permit in a predictable future. To learn the underlying logics and consequences of such limbo and how it is (re)produced in the Swedish migration bureaucracy, this article investigates three data sets: interviews with seven stateless Palestinians, the Swedish Migration Agency’s internal guidelines for the return process, and the same agency’s country reports on stateless people’s situation in the assigned deportation countries. Inspired by Hannah Arendt’s reflections on statelessness and modern bureaucratized societies, the article reveals that there are great challenges to access rights for stateless persons and in holding anyone accountable for decisions adopted by Swedish migration authorities. Moreover, the article shows how limbo induces two interconnected and multilevel technologies in migration authorities: ignorance and repressive consent. As communicating vessels, these technologies form a bureaucratic violence. While diminishing migrants’ access to safety and a dignified life, violence is sustained by legislative changes and insidiously hidden from public debate.